Information Experiences and Needs in Patients with Pulmonary Arterial Hypertension or Chronic Thromboembolic Pulmonary Hypertension - Bodil Ivarsson; Björn Ekmehag; Trygve Sjöberg (Nursing Research and Practice)
Background. Pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) are fatal, noncurable, but treatable diseases that strongly affect the patients. Objective. To describe patients’ experience of information relating to PAH or CTEPH. Methods. A qualitative method using content analysis was applied. Seventeen patients (thirteen women and four men) aged 28–73 years from a regional PAH centre were individually interviewed. Results. Three categories that describe patients’ experiences of information emerged: handling of information, struggling with feelings that also affect others, and vulnerability associated with uncertainty. The patients would have welcomed more information to relatives from the healthcare professionals. Shortcomings on communicating a prognosis were experienced. The mediated information and knowledge gave the patients insight into physical or psychosocial problems. Mutual exchange of information between patients and healthcare professionals were marred by different experiences of attitudes, behaviour, and ownership. Conclusions. In the future, healthcare organizations must struggle to achieve a holistic healthcare by making it more person-centred, and they must also promote cooperation between PAH centres and local healthcare providers. It is essential to determine the most appropriate and valuable path of information and communication and, thereby, the most cost-effective management of PAH or CTEPH.